Molecular Characterization of an IncFIIk Plasmid Co-harboring blaIMP–26 and tet(A) Variant in a Clinical Klebsiella pneumoniae Isolate - Yao, Hong; Cheng, Jing; Li, Aijuan; Yu, Runhao; Zhao, Wenbo; Qin, Shangshang; Du, Xiang-Dang (Frontiers in Microbiology, 2020)
Carbapenems and tigecycline are two important classes of antimicrobial agents to treat the infections caused by Enterobacterales. Here, we reported a plasmid carrying both blaIMP-26 and tet(A) variant in a clinical Klebsiella pneumoniae KP-1572. MIC results showed that K. pneumonia KP-1572 was resistant to a wide range of antimicrobials. The blaIMP-26 and tet(A) variant were located on an identical plasmid, which was indicated by S1-PFGE and southern blotting hybridization and can be successfully transferred by electroporation. Whole plasmid sequencing and analysis revealed that a 142,993 bp plasmid in size, designated pIMP1572, contains an IncFIIk backbone and variable region harboring blaIMP-26 and tet(A) variant. The plasmid pIMP1572 was apparently originated from a tet(A)-carrying IncFIIk plasmid but with a length of 6,216 bp deletion and multiple drug resistance region (MDRR) insertion of 25,259 bp. The plasmid pIMP1572 in the present study represents the first report of IncFIIk plasmid co-carrying blaIMP and tet(A) variant, which should be monitored.